Large strain constitutive modelling of cellulose aerogels. Issue 1 (October 2016) - Rege, Ameya; Itskov, Mikhail
Abstract: In this contribution, we propose a non‐linear constitutive model for cellulose aerogels subject to compression. The model is based on the cellular microstructure of aerogels formed of square shaped unit cells of varying pore sizes with an isotropic spatial distribution. Under uniaxial compression, these cells tend to bend non‐linearly until pore collapse. This cell bending is described by the extended version of the Euler‐Bernoulli beam theory for large deflections. The macroscopic free energy of the whole network is obtained by integration of the microscopic energies of cells over all spatial directions. Cellulose aerogels with different cellulose content are simulated using the proposed model. The model predictions show good agreement with experimental data. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)